Operationalizing the knowledge space: theory, methods and insights for Smart Specialisation - Adam Whittle (Regional Studies, Regional Science, 2020)
Focusing explicitly on the regional dimensions of technological change, this paper examines the technological evolution of Irish NUTS-3 regions. Employing an index of average relatedness, it is shown that over an extended 25-year period (1981–2005) that the production of technological knowledge exhibits a strong path dependency whereby regions are technologically predisposed to diversify into those areas of the knowledge space that are proximate to their current specialization. Implications for the Smart Specialisation thesis are then discussed.